Psychosocial factors affecting pregnancy reactions of primipara in Mianyang - Lin Yuting; Yang Jinghong; Zhang Li (Sichuan jingshen weisheng, 2021)
ObjectiveTo explore the psychosocial factors affecting pregnancy reactions of primipara， so as to alleviate pregnancy reactions in early pregnancy stage.MethodsBasic information scale， Symptom Checklist 90 （SCL-90）， Pregnancy Pressure Scale （PPS） and Pregnancy-unique Quantification of Emesis and Nausea （PUQE） were used to assess the primiparas in a hospital from April to June 2020， thereafter， multiple linear regression was used to screen the main psychosocial factors affecting pregnancy reaction.ResultsA total of 100 pregnant women completed the survey， and the scores of PUQE， PPS and SCL-90 were （4.39±1.14）， （10.89±6.94） and （112.75±22.27）， respectively. Analysis showed that the pregnancy reactions were mild in 93 cases （93%）， moderate in 6 cases （6%） and severe in 1 case （1%）. One-way ANOVA results showed that there was no significant difference in PUQE score among primipara of different age， working status， education levels and average annual family incomes （F=0.57， 0.07， 0.89， 0.51， P>0.05）. Multifactorial regression analysis showed that pregnancy stress， SCL-90 score， obsessive-compulsive symptoms， depression levels， hostility， paranoia and others had statistical significance （P<0.05 or 0.01）.ConclusionThe main psychosocial factors influencing pregnancy reaction are the pregnancy stress and psychosomatic symptoms including obsessive-compulsive symptoms， depression levels， paranoia， hostility， sleep status， diet and others.